High-Speed X-Ray Transmission and Numerical Study of Melt Flows inside the Molten Pool during Laser Welding of Aluminum Alloy. (18th August 2016) - Peng, Jin; Li, Liqun; Lin, Shangyang; Zhang, Furong; Pan, Qinglong; Katayama, Seiji
Abstract : By using the X-ray transmission imaging system, melt flows inside a molten pool were studied during laser welding of aluminum alloy at different welding speeds. Then, the correlation between temperature gradients along the direction of weld penetration and melt flows in the rear part of a molten pool was analyzed by using a three-dimensional numerical method. And the presented model was verified by experimental results. The corresponding investigation was carried out to further study the correlation between temperature gradient and melt flow behavior of the molten pool in the plate heated by preheating temperature. The results indicated that, in the rear part of the molten pool, the maximum flow velocity was located at the bottom of the molten pool. The melt metal in the rear molten pool caused by different welding speeds had significantly different flow trends. As the welding speed increased, the absorbed intensity on the keyhole front wall also increased as well as the recoil pressure that could maintain the keyhole opened. Consequently, the increase of the welding speed was more beneficial to improving the stability of the molten pool.